Discourses on Non-Heteronormative Masculinities and Intimate Partner Violence: a Russian Media Case Study - Andreevskikh, Olga (Journal of family violence, 2024)
Purpose: The current paper is devoted to the analysis of the mediation of non-heteronormative masculinities within discourses on intimate partner violence (IPV) and domestic violence and abuse (DVA) in contemporary Russian media. Methods: The article presents a discourse analysis of five samples of media texts devoted to IPV and/or DVA among LGBTQ people. The media texts were sampled through a keyword search completed on the websites of two openly pro-LGBTQ media outlets (news and entertainment portals Meduza and Takie Dela) and two media outlets catered for predominantly LGBTQ audiences (the news and entertainment portal Parni PLUS and the website of the NGO SPID-Tsentr). Results: The interpretative qualitative analysis of the sampled texts demonstrated that the IPV/DVA survivors’ confessional narratives are framed within wider discourses on non-heteronormative masculinities, which are represented both as transgressing concepts of hegemonic masculinity and as challenging stereotypes about non-heteronormative masculinities. Conclusions: The outcome of the analysis presented in the paper is that there is evidence of the emergence of new media discourses on IPV and DVA among LGBTQ communities. Drawing on feminist discourses on IPV and DVA in heterosexual relationships and using media strategies of LGBTQ coming-out confessional narratives, the sampled media data reveals an ongoing search for a new language of discussing the relatively new societal problem. Further research into mediation of non-heteronormative male survivors of IPV and DVA promises insightful findings concerning the evolution of discourses on non-heteronormative masculinities in contemporary Russian media.